Foetal Echocardiography vs. Neonatal Echocardiography for Diagnosis of Congenital Heart Diseases - Liora, Kevina; Santoso, Tiffanie Almas; Fahira, Siti Alya; Yuliana, Theresia Aquila; Oriza Malta Damayant (PT Inovasi Pratama Internasional, 2023)
Congenital heart disease (CHD) is a structural abnormality in the heart or major intrathoracic blood vessels that has been present since birth. The antenatal detection of congenital cardiac disease has been greatly enhanced by the advent of fetal echocardiography as a crucial component of prenatal ultrasound evaluation. Nevertheless, antenatal CHD diagnosis rates are still lower than those for the majority of other significant structural defects. Aim : Assess the effectiveness of fetal in comparison to neonatal echocardiography. This study is conductedin accordance to the PRISMA statement. Studies were identified from several open-access electronic databases (PubMed Central, ScienceDirect, Google Scholar). Risk of bias of each study was evaluated using Cochrane Risk of Bias In Non-randomized Studies of Interventions (ROBINS-I) tool. Data were descriptively examined and narratively reported. Twelve studies were included in the review. All included studies were considered low-risk. From 12 studies that were included in our study, all recommend fetal echocardiography for prenatal assessment. Lowest reported sensitivity was 64.5%, highest value was 100%. Lowest repoted specificity was 88.9%, highest value was 99.96%. Diagnostic accuracy was reported in 4 studies, with a value of 93 – 99.82% Factors that might be associated with the accuracy of fetal echocardiography are high anatomic complexity, maternal comorbidities, and fellow as initial imager. Fetal echocardiography was found to have a high specificity but limited sensitivity. Low sensitivity suggests that fetal echocardiography results could be inaccurate whereas high specificity means that a negative echocardiography result is often sufficient to predict the absence of CHD. There are some factors that may affect the accuracy of fetal echocardiography, mostly resulting from fetal or maternal factors, such as high complexity of the anomaly, fetal position, late gestation, maternal obesity, and less-esperienced sonographer.